Evaluation of a training programme for interpreters in the field of trauma-focused cognitive behavioural therapy – one year follow-up - Monja Lucia Herold; Lauritz Rudolf Floribert Müller; Rita Rosner (European Journal of Psychotraumatology, 2025)
Background: If the patient does not speak the national language, access to the healthcare system is usually only possible via an interpreter. The need for evaluated training for interpreters working in this field is emphasized in the literature, particularly in the context of psychotherapeutic treatment. This study evaluates a TF-CBT-specific training course for interpreters over a period of one year.Methods: The TF-CBT-specific training was conducted in the form of webinars via the online communication provider Zoom in 10 sessions with 10–15 participants each. The content of the training included the topics of trauma and PTSD, how to establish a constructive working relationship with the therapist, and the modules of TF-CBT with an explanation of the therapeutic principles. In a previous study knowledge gain and a change of an attitude that is more conductive to good cooperation was archived by the workshop in prä-post-tests. In this study the training was evaluated at the 6-month and 12-month follow-up using hierarchical linear regression.Results: Results show that attitude change remained stable over the one-year period. Knowledge and psychotherapy support were statistically significant predictors. Knowledge gained during training decreased over time. Attitude and psychotherapy support were identified as statistically significant predictors.Discussion: The evaluated training for interpreters, who were willing to interpret in a TF-CBT for children and adolescents, showed a stable improvement in attitudes regarding good cooperation with the therapist. Knowledge about PTSD and TF-CBT, did not remain stable over the period of one year after the training. In other comparable training courses, this could be compensated for by consolidation in supervision meetings.